Effect of Endotoxemia Induced by Intraperitoneal Injection of Lipopolysaccharide on the Mg isotopic Composition of Biofluids and Tissues in Mice - Grigoryan, Rosa; Costas-Rodríguez, Marta; Van Wonterghem, Elien; Vandenbroucke, Roosmarijn E.; Vanhaecke, Frank (Frontiers in Medicine, 2021)
Endotoxemia induced in vivo in mice by intraperitoneal injection of lipopolysaccharide (LPS) leads to (neuro)inflammation and sepsis. Also the homeostasis of mineral elements can be altered through mechanisms that still are poorly understood. The isotopic composition of Mg and the concentrations of the minor elements Ca, K, Mg, Na, P and S were determined in biological fluids and tissues of young (14-28 weeks) and aged (40-65 weeks) LPS-injected mice and age-matched controls to reveal potential effects of the LPS-induced infection. Blood plasma of young and aged LPS-injected mice showed a heavy Mg isotopic composition, as well as elevated Mg and P concentrations, compared to matched controls. The plasma Mg isotopic composition was correlated with the P concentration in aged mice. Also the liver Mg isotopic composition was strongly affected in the young and aged LPS-injected mice, while for aged mice, an additional effect on the urine Mg isotopic composition was established. These observations were hypothetically associated with liver inflammation and/or hepatotoxicity, and reduced urinary Mg excretion, respectively. Also a regional endotoxin-induced difference was observed in the brain Mg isotopic composition for the aged mice only, and was attributed to potential disruption of the blood-brain barrier.